2009
DOI: 10.1017/s1138741600001530
|View full text |Cite
|
Sign up to set email alerts
|

Academic Procrastination: Associations with Personal, School, and Family Variables

Abstract: Procrastination is a common behavior, mainly in school settings. Only a few studies have analyzed the associations of academic procrastination with students' personal and family variables. In the present work, we analyzed the impact of socio-personal variables (e.g., parents' education, number of siblings, school grade level, and underachievement) on students' academic procrastination profiles. Two independent samples of 580 and 809 seventh to ninth graders, students attending the last three years of Portugues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
1
20

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 30 publications
(34 reference statements)
3
63
1
20
Order By: Relevance
“…Consequently, we conclude that there is no significant difference between masters' students and PhD students with regards to academic procrastination. This finding is in contrast with that of Rosário et al (2009), who found that there is a significant positive relationship between procrastination and school grade level. Steel (2007) hypothesised that people procrastinate less the older and more learned they become.…”
Section: Discussioncontrasting
confidence: 99%
“…Consequently, we conclude that there is no significant difference between masters' students and PhD students with regards to academic procrastination. This finding is in contrast with that of Rosário et al (2009), who found that there is a significant positive relationship between procrastination and school grade level. Steel (2007) hypothesised that people procrastinate less the older and more learned they become.…”
Section: Discussioncontrasting
confidence: 99%
“…To date, many articles have been published about secondary school or university students cheating and procrastinating behaviour (i. e. Rosário et al, 2009;Vinski & Shick Tryon, 2009). However, to our knowledge, only Roig & deTommaso (1995) have addressed the two characteristics together finding a positive and moderate connection between them.…”
Section: Introductionmentioning
confidence: 99%
“…Enquanto os demais disseram ter começado a procrastinar após a entrada na graduação. Estudos indicam que para muitos, a procrastinação precede a entrada no ensino superior e tende a se estender para a vida profissional (Costa, 2007;Klassen & Kuzucu, 2009;Monteiro, 2009;Rosário et al, 2009). A procrastinação pode ter sua primeira manifestação ainda na infância, na escola, onde ocorre, para maioria dos alunos, a entrada formal numa sociedade competitiva mais ampla.…”
Section: Discussionunclassified